SINTESIS, KARAKTERISASI DAN APLIKASI ELEKTRODA Ti/PbO2 PADA ELEKTRODEGRADASI ZAT WARNA BIRU REAKTIF - , ARIS MUKIMIN, Prof. Dr.rer.nat. Karna Wijaya, M.Eng ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Research on PbO2 electrode synthesis in alkaline conditions has been done. The research aims to improve the electroactive capability of Ti/PbO2 electrode in order to make it potentially applicable for dye degradation by electrolysis. The electrode is synthesized by PbO2 electrodeposition method with low reactant concentration of Pb species (0.0725 mol/L) under alkaline (NaOH) on a Ti plate. Additionally, the electrodeposition process carried out on the potential is 0.5 to 3.4 V. Optimization of synthesis is done by varying the concentration of NaOH (3 to 4.5 M) and the concentration of NaF (0.0048 to 0.0238 M) as a regulator substance. Identification of the properties of the synthesized PbO2 is then determined by the analyses of XRD, EDX, SEM, AAS, and BET. The stability and electrocatalytic properties of the synthesized PbO2 are determined by cyclic voltametry tests using electrolytes: NaCl, H2SO4, CH3NO, H2O, and C2H6O2. The dye of Remazol Brilliant Blue R 19 is used as a model pollutant to determine the electrodegradation activity of the synthesized PbO2 with direct oxidation and indirect oxidation. Direct Oxidation is the degradation of pollutants by the electrode material which releases electrons making up the structure of pollutants while indirect oxidation process through the formation of oxidants by the electrode material. Parameters of time, NaCl concentration, and pH are selected as independent variables in indirect oxidation. Further application of Ti/PbO2 electrode has been done by making an electrocatalytic tube reactor using cylindrical Ti/PbO2 anode. The flow rate and the type of dye are the operating parameters for this reactor. The research indicates that PbO2 electrodeposition on the Ti plate under alkaline and low potential proceeds easily. PbO2 deposit formation rates are influenced by the concentration of NaOH and NaF. The increase in the concentration of NaOH in the region from 3 to 4.5 M will decrease the PbO2 formation rate. This is caused by the presence of increased OH- ions that reduces the abundance of PbO(ad). The addition of F- ions to the concentration of NaF smaller than 0.0095 M will increase the PbO2 formation rate because the resulting positive charge around the anode during electrodeposition is immediately replaced by F- for maintaining electroneutrality, while for the addition of NaF concentration larger than 0.0095 M there is a decline due to competition between the migration force of Pb(OH)3 - and F-. The implications of PbO2 formation rates affect the morphology of the surface, O atom content, crystal shape, and surface physical properties (volume and pore radius). These properties contribute to the electrocatalytic capability of Ti/PbO2 electrode. The roughness of surface morphology, a higher content of O and tetragonal crystal shape are the factors that enhance the ability of the electroactive electrode. Data on degradation of the dye Remazol Brilliant Blue R 19 using synthesized Ti/PbO2 indicates the dependence of the degradation capabilities by the electrode material properties and degradation operating conditions. Alkaline synthesized Ti/PbO2 electrode with its root-shaped surface at the nanoscale, the tetragonal crystal shape and large O atom content have the best capability of degradation. Operating parameters such as NaCl and pH play an important role in the degradation process. Increase in NaCl concentration would increase the formation of an oxidizing agent (Cl2/HClO/ClO-). pH in the range of 5-10 is the optimum condition for the degradation because HClO species is more dominant than the other oxidizing agents (Cl2 and ClO-), where HClO have greater oxidation capabilities. In addition, there is a phenomenon indicates that if the operation is acidic pHâ¤4 or alkaline pHâ¥10, it cause significant losses of Pb on Ti/PbO2 electrode due to the disproportionation and ion exchange reactions. The oxidation level of Cl2/HClO/ClO- is effective in destroying the structure of RB 19, which is evident from the decrease in peak absorption in the UV region. HPLC data suggest that degradation can take up to a perfect form of H2O and CO2 with acetic acid and oxalic acid as intermediate compounds. Degradation of dye RB 19 is also effective for a more applicable reactor design so that the technology is likely to be applied on a field scale.